2019
DOI: 10.3390/met9020143
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Limit Improvement and Rendering Defects Harmless by Needle Peening for High Tensile Steel Welded Joint

Abstract: The effects of needle peening (NP) on the bending fatigue limit of a high tensile steel (HTS) HT780 (JIS-SHY685)-welded joint containing an artificial semicircular slit on the weld toe were investigated. Three-point bending fatigue tests were conducted at a stress ratio of R = 0.05 for NP-treated welded specimens with and without a slit. The fatigue limits of all specimens increased by 9-200% due to the NP treatment. Furthermore, NP-treated specimens with slit depths of a = 1.0 mm exhibited high fatigue limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Takahashi et al clarified that the fatigue strength of spring steel specimens with artificial surface defects could be improved with SP by the same level as that attained in the cases of defect‐free steel specimens subjected to the same SP . Similar effects of SP and needle peening have been reported in various other materials for the rendering of harmless surface defects . Specifically, Takahashi et al clarified that semicircular slits with depths of 0.1 mm in the aluminum alloy A7075‐T651 could be rendered harmless by performing SP .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Takahashi et al clarified that the fatigue strength of spring steel specimens with artificial surface defects could be improved with SP by the same level as that attained in the cases of defect‐free steel specimens subjected to the same SP . Similar effects of SP and needle peening have been reported in various other materials for the rendering of harmless surface defects . Specifically, Takahashi et al clarified that semicircular slits with depths of 0.1 mm in the aluminum alloy A7075‐T651 could be rendered harmless by performing SP .…”
Section: Introductionmentioning
confidence: 82%
“…14,15 Similar effects of SP and needle peening have been reported in various other materials for the rendering of harmless surface defects. [16][17][18] Specifically, Takahashi et al clarified that semicircular slits with depths of 0.1 mm in the aluminum alloy A7075-T651 could be rendered harmless by performing SP. 19 Several studies have shown that the propagation of fatigue cracks in aluminum alloys is delayed by applying LP at the tip of these cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Leitner et al [5] analyze how overloads induce fatigue crack growth retardation on EA47 steel round bars containing semi-elliptical cracks, comparing the experimental results to the predictions provided by a modified NASGRO equation. Finally, Fueki et al [6] evaluates the fatigue limit improvement caused by needle peening in high tensile (strength) steel HT780. All these contributions cover different sectors, such as aerospace, railway, bridge design, or energy generation, among others.…”
Section: Contributionsmentioning
confidence: 99%
“…Therefore, if the surface defects can be rendered harmless in terms of the fatigue limit through peening, the reliability of additive-manufactured metals can be improved, which can contribute to the increased industrial usage of additive-manufactured parts. Surface defects can be rendered harmless through various types of peening on conventionally manufactured metals [22][23][24][25]. Takahashi et al reported that a semicircular surface defect with a less than 0.2 mm depth could be rendered harmless by applying SP to spring steel [22].…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi et al reported that a semicircular surface defect with a less than 0.2 mm depth could be rendered harmless by applying SP to spring steel [22]. Fueki et al clarified that a semicircular surface defect with a depth of less than 1 mm could be rendered harmless by applying needle peening to high-tensile steel-welded joints [23]. Takahashi et al compared the maximum defect size that can be rendered harmless by SP and cavitation peening (CP) in 7075 aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%